THE EFFECT OF THE USE OF WORDWALL AND CANVA LEARNING MEDIA AND LEARNING MOTIVATION ON THE COGNITIVE DEVELOPMENT OF 5-6 YEAR-OLD CHILDREN AT DHARMA WANITA PUGERAN KINDERGARTEN - Finisya Seffy Christiyanti; Rufi'i Rufi'i; Reza Rachmadtullah (Jurnal Visipena, 2025)
Cognitive development is an important aspect in the learning process, so choosing the right media is a key factor in supporting the effectiveness of early childhood learning. This study aims to analyze the effect of the use of Wordwall and Canva media and learning motivation on the cognitive development of children aged 5–6 years at Dharma Wanita Pugeran Kindergarten. The research design used a quasi-experiment with Two-Way ANOVA, involving 30 students divided into two treatment groups. The results showed that learning media had a significant effect on cognitive development (F = 55.60; p < 0.05), where Wordwall produced a higher increase than Canva. Conversely, learning motivation did not have a significant effect (F = 0.310; p > 0.05) and there was no interaction between learning media and motivation (F = 2.737; p > 0.05). The research model explained 73% of the variation in cognitive development. These findings confirm that Wordwall is more effective in improving children's cognitive abilities, regardless of their initial motivation level. Practically, these results recommend that teachers integrate gamification media such as Wordwall in early childhood learning to maximize cognitive achievement consistently.